Nicotine regulates the expression of UDP-glucuronosyltransferase (UGT) in humanized UGT1 mouse brain() - Sakamoto, Masaya (Drug Metab Pharmacokinet, 2015)
UDP-glucuronosyltransferase (UGT) is a family of enzymes that catalyze the glucuronidation of various compounds, and thereby has an important role in metabolism and detoxification of a large number of xenobiotic and endogenous compounds. UGTs are present highly in the liver and small intestine, while several investigations on quantification of UGT mRNA reported that UGTs were also expressed in the brain. However, reported expression patterns of UGT isoforms in human brain were often incongruous with each other. In the present study, therefore, we investigated UGT mRNA expressions in brains of humanized UGT1 (hUGT1) mice. We found that among the human UGT1 members, UGT1A1, 1A3, and 1A6 were expressed in the brain. We further observed that nicotine (3 mg/kg) induced the expression of UGT1A3 mRNA in the brain, but not liver. While it was not statistically significant, the nicotine treatment resulted in an increase in the chenodeoxycholic acid glucuronide-formation activity in the brain microsomes. UGT1A3 is involved in metabolism of various antidepressants and non-steroidal antiin-flammatory drugs, which exhibit their pharmacological effects in the brain. Therefore, nicotine-treated hUGT1 mice might be useful to investigate the role of brain UGT1A3 in the regulation of local levels of these drugs and their response.